Effect of the Surgical Safety Checklist on the incidence of adverse events: contributions from a national study - LUCIANE RIBEIRO DE FARIA; TIAGO RICARDO MOREIRA; FÁBIO DA COSTA CARBOGIM; RONALDO ROCHA BASTOS (Revista do Colégio Brasileiro de Cirurgiões, 2022)
ABSTRACT Objective: the study evaluated the effect of using the safe surgery checklist (CL) on the incidence of adverse events (AE). Methods: cross-sectional and retrospective research with 851 patients undergoing surgical procedures in 2012 (n=428) and 2015 (n=423), representing the periods before and after CL implantation. The AE incidences for each year were estimated and compared. The association between the occurrence of AE and the presence of CL in the medical record was analyzed. Results: a reduction in the point estimate of AE was observed from 13.6% (before using the CL) to 11.8% (with the use of the CL). The difference between the proportions of AE in the periods before and after the use of CL was not significant (p=0.213). The occurrence of AE showed association with the following characteristics: anesthetic risk of the patient, length of stay, surgery time and classification of the procedure according to the potential for contamination. Considering the proportion of deaths, there was a significant reduction in deaths (p=0.007) in patients whose CL was used when compared to those without the use of the instrument. There was no significant association between the presence of CL and the occurrence of AE. It was concluded that the presence of CL in the medical record did not guarantee an expected reduction in the incidence of AE. Conclusion: however, it is believed that the use of the instrument integrated with other patient safety strategies can improve the safety/quality of surgical care in the long term.